In vivo performance and carcass traits of Nero Siciliano pigs reared outdoors and in plein air - Chiofalo V.; Zumbo A.; Liotta L.; Chiofalo B. (5. International Symposium on the Mediterranean Pig, 2007)
In vivo and post mortem performances of Nero Siciliano pigs reared outdoors and plein air were studied. Thirty pigs were divided into two homogeneous groups, outdoors (OD, with access only to natural resources) and plein air (PA, fed with concentrate feed), in relation to the breeding system. Pigs were slaughtered at 80 kg of BW, on average. Carcass yield was calculated. The right sides were dissected into lean, fat and bone cuts. A loin sample was dissected into the major tissues. The OD group reached the slaughter weight after 250 days and the PA group after 160 days from the beginning of the trial. The slaughter yield between two groups (PA 83% vs OD 71%) was statistically significant. The backfat thickness was higher in PA (6.4 cm) than in the OD (2.45 cm) group. The rearing system influenced significantly (P=0.05) the composition of loin sample for fat (PA 5.16% vs OD 3.43%).
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)